Human impact on the forest line - Salmonsson, Jonas (2004)
The vegetation in the Swedish Scandes has been considered to be mostly unaffected in the past by humans. Thus, the region has been regarded as important when studying how climate chang affects forest line vegetation. However, recent evidence from archaeological surveys in the Scandes show that the area have been used to a much larger extent than previously belived. The aim of this study was to examine past vegetation changes at the forest line right next to seven stalo dwellings in the Vindelfjällen area, northern Sweden, by the use of pollenanalysis. The results show that around the dwellings a deforestation occurred locally and the altitude of the forest line was lowered. Also, a chatastophic shift in the ecosystem might have occured that reduced the ability of the forest to regenerate. To understand how climate affects the forest line today we have to choose study areas where past human impact has been minimal.